Recommendations for local-regional anesthesia during the COVID-19 pandemic - Lima,Rodrigo Moreira e (2020)
Abstract Since the beginning of the COVID-19 pandemic, many questions have come up regarding safe anesthesia management of patients with the disease. Regional anesthesia, whether peripheral nerve or neuraxial, is a safe alternative for managing patients with COVID-19, by choosing modalities that mitigate pulmonary function involvement. Adopting regional anesthesia mitigates adverse effects in the post-operative period and provides safety to patients and teams, as long as there is compliance with individual protection and interpersonal transmission care measures. Respecting contra-indications and judicial use of safety techniques and norms are essential. The present manuscript aims to review the evidence available on regional anesthesia for patients with COVID-19 and offer practical recommendations for safe and efficient performance.